RETRACTED ARTICLE: A Zinc Morpholine Complex Prevents HCl/Ethanol-Induced Gastric Ulcers in a Rat Model - Suzy M. Salama; Nura Suleiman Gwaram; Ahmed S. AlRashdi; Shaden A. M. Khalifa; Mahmood A. Abdulla; Hapipah M. Ali; Hesham R. El-Seedi (Scientific Reports, 2016)
Abstract Zinc is a naturally occurring element with roles in wound healing and rescuing tissue integrity, particularly in the gastrointestinal system, where it can be detected in the mucosal and submucosal layers. Zinc chelates are known to have beneficial effects on the gastrointestinal mucosa and in cases of gastric ulcer. We synthesized complexes of zinc featuring a heterocyclic amine binding amino acids then investigated their ability to enhance the gastric self-repair. Zinc-morpholine complex, Zn(L)SCN, namely showed strong free-radical scavenging, promotion of the DNA and RNA polymerases reconstruction and suppression of cell damage. The complex’s mode of action is proposed to involve hydrogen bond formation via its bis(thiocyanato-k)zinc moiety. Zn(L)SCN complex had potent effects on gastric enzymatic activity both in vitro and in vivo. The complex disrupted the ulcerative process as demonstrated by changes in the intermediate metabolites of the oxidative pathway – specifically, reduction in the MDA levels and elevation of reduced glutathione together with an attenuation of oxidative DNA damage. Additionally, Zn(L)SCN restored the gastric mucosa, inhibited the production of pro-inflammatory cytokines (IL-6, TNF and the caspases), and preserved the gastric mucous balance. Zn(L)SCN thus exhibited anti-oxidative, anti-inflammatory and anti-apoptotic activities, all of which have cytoprotective effects on the gastric lining.